Мовна проблематика епістолярію Бориса Грінченка - Найрулін, А.О. (Лексикографічний бюлетень, 2014)
The article deals with the analysis of the linguistic subject matter of the epistolary of Borys Hrynchenko based on the material of his letters to Vladymyr Hnatiuk, Trofym Zinkivskyi and Mykhailo Kotsiubynsky. It has been emphasized that the lexicographic activity of B. Hrynchenko appeared an example and proof of his intensive and self-sacrifi cing labor, and it is no wonder why the Dictionary of the Ukrainian language remains the basis for the fundamental lexicographic works of the domestic scholars even in our days. Th e epistolary heritage of B. Hrynchenko pays a great att ention to the problems of the lexical, grammatical, accentuational, and orphographic normalization of our literary language, the educational function of our mother tongue and its use in the sphere of science.